Epilepsy Association with Infantile Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The prevalence and types of epilepsy and other CNS diseases among 118 individuals diagnosed as children (median age 4 years) with infantile autism (IA) and 336 matched controls from the general population were determined in a longitudinal study at Bispebjerg University Hospital, Copenhagen, and Glostrup University Hospital, Denmark.